Social Media as a Tool for the Sustainability of Small and Medium Businesses in Macedonia - Veseli-Kurtishi, Teuta (European Journal of Sustainable Development, 2018)
Social media is considered as the main marketing tool for an SME and has shown significant growth in effectiveness lately, as well as in the business sustainability all over the word. Businesses are acknowledging the potential of social media because they do not really exist online if they are not represented across all social channels – and regularly interacting with their followers, journalists who cover the industry, leaders and tastemakers, etc. The main purpose of this research is to analyze some of the SME operating in Macedonia and to find answers about the true effectiveness of social media marketing and their impact on the sustainability of businesses. Using a firm level survey in 244 businesses in Macedonia we investigate the impact of social media marketing on the sustainability of businesses. Results indicate that there is a positive impact of social media marketing on business effectiveness and sustainability, however social media in Macedonia are still in the early stages and there are opportunities for improvement. Keywords: Marketing, Social Media, Sustainability, SME, Effectiveness.